1999
DOI: 10.1111/1469-8986.3620233
|View full text |Cite
|
Sign up to set email alerts
|

How many nights are enough? The short‐term stability of sleep parameters in elderly insomniacs and normal sleepers

Abstract: Temporal stability is an important fundamental quality when measuring sleep parameters, yet it has been infrequently assessed. Generalizability theory was used to estimate the short-term temporal stability of five variables commonly used to characterize insomnia: sleep onset latency, total sleep time, wake after sleep onset, time in bed, and sleep efficiency. Estimates were calculated for 32 elderly primary insomniacs and 32 elderly normal sleepers, both in the lab and at home, using both sleep logs and polyso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
68
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(68 citation statements)
references
References 10 publications
0
68
0
Order By: Relevance
“…Repeated assessments would provide a more reliable assessment of the regular sleep of the participants as well as the frequency with which they experienced sleep problems. The number of nights necessary for such reliability can vary from five nights to three weeks depending on the methodology (Acebo et al, 1999;Wohlgemuth et al, 1999). Objective measurements of sleep such as polysomnography and actigraphy would be useful.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Repeated assessments would provide a more reliable assessment of the regular sleep of the participants as well as the frequency with which they experienced sleep problems. The number of nights necessary for such reliability can vary from five nights to three weeks depending on the methodology (Acebo et al, 1999;Wohlgemuth et al, 1999). Objective measurements of sleep such as polysomnography and actigraphy would be useful.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…While significant selfreport differences in sleep time between older adults with and without insomnia complaints have been observed in most of these studies, the objective sleep findings have been more equivocal. Indeed, some studies have found no statistically significant differences in polysomnographic sleep parameters between older adults with and without insomnia (Bastien et al, 2003;Edinger et al, 1997;Wohlgemuth et al, 1999). These studies had approximately 30 or fewer older adults in each group, thus while there were potential clinically significant differences in some objective domains, they were not statistically significant.…”
Section: Introductionmentioning
confidence: 96%
“…Furthermore, the circadian output that influences sleep-wake cycles may be weaker in older adults, thus leading to more frequent objective sleep-to-wake transitions (Klerman et al, 2004). While several studies have compared the subjective and objective polysomnographic sleep characteristics of older adults with insomnia complaints, most have relied on a single-night polysomnography assessment (Bastien et al, 2003;Unruh et al, 2008), included middle-aged research study participants (Means et al, 2003), excluded study participants with other medical conditions (Edinger et al, 1997;Wohlgemuth et al, 1999), or did not include a control arm (Libman et al, 1997;Riedel and Lichstein, 1998;Riedel et al, 2001). While significant selfreport differences in sleep time between older adults with and without insomnia complaints have been observed in most of these studies, the objective sleep findings have been more equivocal.…”
Section: Introductionmentioning
confidence: 99%
“…Insomnia is commonly conceptualized as a periodic disorder characterized by sleep variability. Whereas some insomnia sufferers exhibit a somewhat constant pattern of poor sleep (Valliè res et al, 2011), the majority of insomnia sufferers show some night-to-night fluctuations, with poor nights of sleep followed typically by good ones, and vice versa (Perlis et al, 2010;Wohlgemuth et al, 1999). The putative mechanisms proposed to explain this phenomenon include voluntary behaviours, such as increasing time in bed to compensate for a previous poor night of sleep, as well as homeostatic processes, which lead eventually to ÔrecoveryÕ sleep after one or several poor nights (Espie, 2002).…”
Section: Introductionmentioning
confidence: 99%